Advances in Cultural Tourism Research Proceedings of the International Conference on Cultural Tourism Advances, June 2023, Belgium - Neuts, Bart; Martins, João; Ioannides, Marinos (Advances in Digital and Cultural Tourism Management, 2025)
XIV, 230 p. 69 illus., 65 illus. in color.